Development of guidelines for managing unused and expired medications in local communities: An engaged stakeholder waste hierarchy approach - Patranit Srijuntrapun; Kusawadee Maluangnon (PLoS ONE, 2026)
Objectives The management of unused and expired medications is essential to address environmental pollution, ensure public health safety, and optimize healthcare resources. Proper disposal of medications is especially challenging in areas where there is a lack of organized take-back programs. To bridge this gap, this study aims to develop inclusive guidelines through collaborative stakeholder engagement, while recognizing the absence of universally applicable solutions. Methods The study uses a mixed-methods approach, relying on surveys, in-depth interviews, and focus groups. First, 156 households were surveyed to measure the amount and economic value of unused and expired medications in their possession. Subsequently, in-depth interviews were conducted with 45 participants, including healthcare professionals, community leaders, citizens, and policymakers. These in-depth interviews provided rich insights about the roles, local contexts, and challenges regarding the management of unused and expired medications. Lastly, focus group discussions with 16 participants provided the basis for the development of a new set of guidelines aligned with waste hierarchy principles and founded on a holistic view of the medication cycle, from acquisition to disposal. Results The findings of the study have revealed that blood glucose lowering agents are the most common type of unused medication kept by households, while anti-hypertensive drugs are the ones that most frequently expire. In addition, the study has shown that medication wastage occurs at multiple stages across the system. Building on these insights, a set of guidelines and community-based management pathways were developed, offering a practical and scalable model in seven steps that can be applied to environments with no formal take-back systems. Conclusions The guidelines presented in this study offer a practical and effective framework for policymakers, researchers, and practitioners focused on regions that lack formal disposal mechanisms to guide community-based medication wastage reduction and disposal practices, supporting the sustainable production and consumption of medications.